Models at Different Scales. A Study on the Inference in the Perception of the Relationship between Space, Body, and Object (diségno, 2024)
The debate of the predominance between drawing and model as design tools is as old as Architecture itself. Up to our days, we cannot deny the centralism of drawings in the process of ideation, configuration, and communication of architecture, but the use of models has never disappeared because both elements result to be complementary.Is widely known how drawings change in concretion depending on the scale. There is no research if the same thing occurs with models. Basing the study on the works done by students along four courses in an Interior Architecture Degree, this paper delves into the mechanisms of perception behind scale inference in architectural models and discusses their implications for design practice.
Keywords: Models; Scale; Perception; Detail